Konsep Mahar dalam Surah An-Nisa Ayat 4: Pendekatan Maqasid Al-Qur’an dalam Perspektif Rasyid Ridha - Nafilah Sulfa; Nafilatul Khair (Al Karima : Jurnal Studi Ilmu Al Quran dan Tafsir, 2025)
This research is motivated by the attention of researchers to the current dowry problem which according to researchesrs is very irrelevant to sharia recommendation and provisions. Which at the time the dowryis more emphasized on the basis of interest and profit. This type of researchesr uses library researchesr or library researchesr. The data collection method used is the documentation method. Meanwhile, the analytical method used is the maudhui/thematic method, namely examining verses that have the same discussion and then compiling them into a discussion. The result of researchesr conducted by researchesrs on surah an-nisa verse 4 are: according to Rashid Ridha, dowry is something that is given by a man to a woman sincerely without any element of coercion and is an obligation due to marriage. A husband may not take anything from a wife except for the pleasure of a wife. Mahar is something tha is the right of a wife as compentation for the pleasure that wil be felt by a husband after they do the marriage.